Liftoff of a 60mg flapping-wing MAV - Wood, R.J. (2007 IEEE/RSJ International Conference on Intelligent Robots and Systems, 2007)
Up to this point, researchers working to artificially re-create hovering insect flight have not demonstrated an integrated micromechanical device that is able to lift its own weight. Inspiration from biological systems coupled with revolutionary breakthroughs in microfabrication technologies have now enabled the realization of insect- sized micro air vehicles (MAVs). This work describes a solution to the mechanical and aeromechanical components of an insect-scale MAV by demonstrating a 60 mg structure that can generate sufficient lift to takeoff with external power and constrained body degrees of freedom.